2008
DOI: 10.1021/jp8067188
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Solvent Solubility Parameters on the Dispersion of Single-Walled Carbon Nanotubes

Abstract: A systematic study of the effect of a series of organic solvents on the dispersion of as-produced HiPco single-walled carbon nanotubes (SWNTs) has been conducted. UV−vis−NIR absorption spectroscopy coupled with an integrating sphere was employed to differentiate absorbance and scattering. For each solvent, a concentration-dependent study of the absorbance in the normal chamber and in the integrating sphere enabled the calculation of the total extinction coefficient and absorption coefficient. A correlation bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 26 publications
1
56
0
Order By: Relevance
“…Measurements were performed using an integrating sphere to minimize the contributions of scattering to the measured extinction 8,22 . 10-millimeter quartz cuvettes were used for all the measurements.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Measurements were performed using an integrating sphere to minimize the contributions of scattering to the measured extinction 8,22 . 10-millimeter quartz cuvettes were used for all the measurements.…”
Section: Methodsmentioning
confidence: 99%
“…UV-vis-NIR measurements were carried out on the whole sample before centrifugation (immediately before measurement all samples were vigorously shaken) but only on the supernatant after centrifugation, so that the mass fraction of aggregates can be estimated (see Equation 1). The absorbance at a wavelength of 660 nm was used for all the calculations 6,8,21 .…”
Section: Methodsmentioning
confidence: 99%
“…In comparison with DMF and NMP, an improvement in the dispersion limit of SWCNTs has been observed for alkyl amide solvents, such as N,N-dimethylacetamide (DMAc), N,N-dimethylpropanamide (DMP) and N,N-diethylacetamide (DEA), and is attributable to the highly polar π-system in conjunction with their optimal geometries (appropriate bond lengths and bond angles) [68]. In addition, chlorinated aromatic solvents, such as mono-chlorobenzene, ortho-dichlorobenzene (ODCB), meta-dichlorobenzene and 1,2,4-trichlorobenzene, have been demonstrated to be efficient at dispersing SWCNTs [69,70]. However, it has been found that phenyl rings within solvent molecules are not the dominant factor in obtaining stable SWCNTs dispersions [71].…”
Section: Carbon Nanotubes In Imidazolium Ionic Liquidsmentioning
confidence: 99%
“…The dispersion quality of CNTs in solvents is also affected by the nanotube concentration and processing techniques as well as the physical parameters of as-produced CNTs [68,69,71]. However, "stable suspensions" of SWCNTs in the best organic solvents (DMF and NMP) still aggregate on a time-scale of days, even minutes, in the absence of any external agents [64].…”
Section: Carbon Nanotubes In Imidazolium Ionic Liquidsmentioning
confidence: 99%
“…Subsequently, the dispersibility of SWNTs in chlorinated aromatic solvents and other solvents reported in literature, including dimethylformamide (DMF) [5,6], 1,2-dichloroehtane (DCE) [7], chloroform [2], and toluene [8], in terms of optical extinction and absorption coefficients, was compared as a function of Hildebrand and Hansen solubility parameters [9].…”
Section: Introductionmentioning
confidence: 99%